Improved method increases sensitivity for circulating hepatocellular carcinoma cells - Liu, Hui-Ying (World J Gastroenterol, 2015)
AIM: To improve an asialoglycoprotein receptor (ASGPR)-based enrichment method for detection of circulating tumor cells (CTCs) of hepatocellular carcinoma (HCC). METHODS: Peripheral blood samples were collected from healthy subjects, patients with HCC or various other cancers, and patients with hepatic lesions or hepatitis. CTCs were enriched from whole blood by extracting CD45-expressing leukocytes with monoclonal antibody coated-beads following density gradient centrifugation. The remaining cells were cytocentrifuged on polylysine-coated slides. Isolated cells were treated by triple immunofluorescence staining with CD45 antibody and a combination of antibodies against ASGPR and carbamoyl phosphate synthetase 1 (CPS1), used as liver-specific markers, and costained with DAPI. The cell slide was imaged and stained tumor cells that met preset criteria were counted. Recovery, sensitivity and specificity of the detection methods were determined and compared by spiking experiments with various types of cultured human tumor cell lines. Expression of ASGPR and CPS1 in cultured tumor cells and tumor tissue specimens was analyzed by flow cytometry and triple immunofluorescence staining, respectively. RESULTS: CD45 depletion of leukocytes resulted in a significantly greater recovery of multiple amounts of spiked HCC cells than the ASGPR(+) selection (Ps < 0.05). The expression rates of either ASGPR or CPS1 were different in various liver cancer cell lines, ranging between 18% and 99% for ASGPR and between 9% and 98% for CPS1. In both human HCC tissues and liver cancer cell lines, there were a few HCC cells that did not stain positive for ASGPR or CPS1. The mixture of monoclonal antibodies against ASGPR and CPS1 identified more HCC cells than either antibody alone. However, these antibodies did not detect any tumor cells in blood samples spiked with the human breast cancer cell line MCF-7 and the human renal cancer cell line A498. ASGPR(+) or/and CPS1(+) CTCs were detected in 29/32 (91%) patients with HCC, but not in patients with any other kind of cancer or any of the other test subjects. Furthermore, the improved method detected a higher CTC count in all patients examined than did the previous method (P = 0.001), and consistently achieved 12%-21% higher sensitivity of CTC detection in all seven HCC patients with more than 40 CTCs. CONCLUSION: Negative depletion enrichment combined with identification using a mixture of antibodies against ASGPR and CPS1 improves sensitivity and specificity for detecting circulating HCC cells.